Transcriptome Profiling to the Effects of Drought Stress on Different Propagation Modes of Tea Plant (Camellia sinensis) - Ding, Zhou; Jiang, Changjun (Frontiers in Genetics, 2022)
Tea plant (Camellia sinensis) is an important economic beverage crop. Drought stress can have serious adverse effects on tea trees, which hinders the growth and metabolism of tea trees at various stages. In this paper, the molecular adaptive mechanism of sexual progeny and asexual reproduction of tee trees to drought stress was studied based on transcriptome sequencing. After analyzing the experimental data, it was found that the comparison between the sexually active progeny and the asexual reproduction progeny of tea trees. It showed that there were many levels of up-regulation and down-regulation of genes related to cell components, molecular functions and biological processes. The functional alterations focus on a variety of metabolic pathways such as biosynthesis of phenylpropanoid, biosynthesis of secondary metabolism, metabolism of starch and sucrose, conversion of pentose and glucuronic acid. The transcriptome analysis also indicated that moderate drought stress had significant effects on the expression of related genes in the synthesis of pro, SOD and POD of tea roots, and the expression of these genes was up-regulated and down-regulated in different degrees. Further studies on these differentially expressed genes will lay the foundation on upgrading cultivation methods and biotechnology breeding for improving the quality of tea trees.